2013
DOI: 10.1093/jxb/ert148
|View full text |Cite
|
Sign up to set email alerts
|

Differential accumulation of phenolic compounds and expression of related genes in black- and yellow-seeded Brassica napus

Abstract: Developing yellow-seeded Brassica napus (rapeseed) with improved qualities is a major breeding goal. The intermediate and final metabolites of the phenylpropanoid and flavonoid pathways affect not only oil quality but also seed coat colour of B. napus. Here, the accumulation of phenolic compounds was analysed in the seed coats of black-seeded (ZY821) and yellow-seeded (GH06) B. napus. Using toluidine blue O staining and liquid chromatography–mass spectrometry, histochemical and biochemical differences were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
138
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 72 publications
17
138
0
Order By: Relevance
“…Yellow B. napus seeds are the most desirable, as they have thinner seed coats and higher seed oil and protein contents than do the dark-seeded varieties with a similar genetic background (Olsson, 1960; Tang et al, 1997; Meng et al, 1998). Several studies have shown that seed coat color is determined by the content of the phenolic compounds cyanidin and procyanidin in B. napus (Marles and Gruber, 2004; Lepiniec et al, 2006; Qu et al, 2013). These pigments are mainly composed of polymers of proanthocyanidin (PA), which is synthesized via the flavonoid-anthocyanin-proanthocyanidin pathway (simplified as flavonoid pathway here), a core branch of the phenylpropanoid pathway (Bharti and Khurana, 2003; Gachon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Yellow B. napus seeds are the most desirable, as they have thinner seed coats and higher seed oil and protein contents than do the dark-seeded varieties with a similar genetic background (Olsson, 1960; Tang et al, 1997; Meng et al, 1998). Several studies have shown that seed coat color is determined by the content of the phenolic compounds cyanidin and procyanidin in B. napus (Marles and Gruber, 2004; Lepiniec et al, 2006; Qu et al, 2013). These pigments are mainly composed of polymers of proanthocyanidin (PA), which is synthesized via the flavonoid-anthocyanin-proanthocyanidin pathway (simplified as flavonoid pathway here), a core branch of the phenylpropanoid pathway (Bharti and Khurana, 2003; Gachon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The observed diversity of seed coat color in rapeseed is caused by the differential accumulation of pigments in the endothelium [9,33], which is similar to the TT phenotype in A . thaliana [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Defects in different TT genes result in different degrees of variation in testa color [36]. Moreover, considering the close phylogenetic relationship between Arabidopsis and Brassica , orthologs of TT genes may play similar roles in Brassica species; quantitative analysis of gene expression supports this inference [33,38]. In A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allotetraploid species B. napus, which was derived from the interspecific hybridization of two diploid species, B. rapa and B. oleracea, is an ideal model for the study of gene evolution and function. In addition, excessive gene loss is typical following polyploid formation in eukaryotes (Qu et al, 2013). In this study, all copies of GLK1 identified were verified using the homology cloning method, and each of the orthologous blocks corresponding to ancestral blocks was identified using collinearity between Brassicaceae orthologs (Table S3).…”
Section: Triplication Analysis Of Glk1 Genesmentioning
confidence: 99%